2005
DOI: 10.1007/s11255-005-4012-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Pulmonary Infections in Renal Transplant Recipients in the Tropics: A Single Center Study

Abstract: Our study has shown that more than 1/3rd of pulmonary infections in renal transplant recipients can be attributed to multiple organisms. Bacterial infections were the commonest cause of post transplant pulmonary infection. Tuberculosis is common cause of pulmonary infection in these patients in our set up. Because of its high diagnostic yield, BAL should be considered in all patients with suspected pulmonary infections in the post transplant period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…It would be prudent to practice a low threshold for early invasive diagnostic evaluation as a delay in diagnosis can lead to rapid deterioration and poor outcomes in immunocompromised patients. Bacterial infections are the predominant cause of pneumonia in renal transplant recipients [10,12–15] and this was also evident in our study (29.4%). They occurred throughout the post‐transplant course highlighting the susceptibility of immunocompromised patients to community‐acquired infections.…”
Section: Discussionsupporting
confidence: 83%
“…It would be prudent to practice a low threshold for early invasive diagnostic evaluation as a delay in diagnosis can lead to rapid deterioration and poor outcomes in immunocompromised patients. Bacterial infections are the predominant cause of pneumonia in renal transplant recipients [10,12–15] and this was also evident in our study (29.4%). They occurred throughout the post‐transplant course highlighting the susceptibility of immunocompromised patients to community‐acquired infections.…”
Section: Discussionsupporting
confidence: 83%
“…Among renal transplant recipients with lung infiltrates, invasive procedures such as bronchoalveolar lavage has a diagnostic yield of 75.8%. 11 In both of our cases, the diagnosis was made through culture of bronchial washings alone and all other clinical specimens like sputum and pleural fluid, blood, bone marrow were negative. The only smear to show nocardial species was the Gram and modified Kinyoun staining of bronchial washings in case no.…”
Section: Discussionmentioning
confidence: 70%
“…Jha V et al 13 reported an incidence of 30.7%. Vikram Kalra et al 14 found the incidence of tuberculosis in post-renal transplant patients to be 36.3%. As quoted in the previous study, this is probably because of the use of bronchoscopy in the isolation of the organism in the recent studies.…”
Section: Discussionmentioning
confidence: 99%